MODELING AND OPTMIZATION POWER REQUIREMENTS OF ACTIVE ACOUSTIC LOUVRES - Maciel, M. A.; Zuffi, G. A.; Duarte, M. A. V. (Revista de Engenharia Térmica, 2015)
The development of new technologies for ventilated facades is within the context of energy efficiency of buildings , including the compatibility of the dichotomy between natural ventilation and soundproofing in tropical countries . Given this perspective, this work proposes the application of techniques for active noise control in acoustic louvers . One limitation of the spread of technical active noise control in buildings is the energy inherent in the technique. Thus, the proposed system is based on the reduction of structural vibrations of the shutter blades by using piezoelectric actuators . The acoustic transmission loss and energy requirements for active shutters are investigated from numerical modeling . The results suggest their technical feasibility with superior soundproofing to 30 dB and power consumption less than 35 W. Thus , the active noise control using piezoelectric actuators is presented as a promising technology , aligning soundproofing with low energy consumption Type the text of the abstract here, Times New Roman, 9, lower case letters, justified paragraphs, 1.0 line spacing. The abstract should state the objectives, methodology and main conclusions in 200 to 300 words. No not divide into paragraphs.